2019
DOI: 10.1186/s12864-019-6420-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic selection for non-key traits in radiata pine when the documented pedigree is corrected using DNA marker information

Abstract: BackgroundNon-key traits (NKTs) in radiata pine (Pinus radiata D. Don) refer to traits other than growth, wood density and stiffness, but still of interest to breeders. Branch-cluster frequency, stem straightness, external resin bleeding and internal checking are examples of such traits and are targeted for improvement in radiata pine research programmes. Genomic selection can be conducted before the performance of selection candidates is available so that generation intervals can be reduced. Radiata pine is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…GBS marker information has been successfully used for parentage reconstruction in Scots pine [ 34 ], as well as to perform genomic predictions studies in livestock [ 35 , 36 ], maize [ 37 ], wheat [ 33 ], soybean [ 38 ], Picea glauca (Moench) Voss × Picea engelmannii Parry ex Engelm. [ 39 ] and radiata pine [ 40 ]. Therefore, GBS is an attractive technology that can be used to perform GS and genome-wide association studies (GWAS) for Scots pine [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…GBS marker information has been successfully used for parentage reconstruction in Scots pine [ 34 ], as well as to perform genomic predictions studies in livestock [ 35 , 36 ], maize [ 37 ], wheat [ 33 ], soybean [ 38 ], Picea glauca (Moench) Voss × Picea engelmannii Parry ex Engelm. [ 39 ] and radiata pine [ 40 ]. Therefore, GBS is an attractive technology that can be used to perform GS and genome-wide association studies (GWAS) for Scots pine [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trait data must be in Linkage Disequilibrium-LD or genetic auto-correlation (e.g., Kelleher et al, 2012), with the molecular markers or with the samples' genetic co-ancestry. GP utility has been demonstrated ( Table 1) in model forest tree species such as Eucalyptus Suontama et al, 2019), and conifers as Pinus Li et al, 2019) and Douglas-fir (Thistlethwaite et al, 2017(Thistlethwaite et al, , 2019b, but also in non-model perennial crops such as coffee (Sousa et al, 2018), rubber (Cros et al, 2019;Souza et al, 2019) and oil palm (Cros et al, 2015). GP may even fit epigenetics (Roudbar et al, 2020), as well as multi-trait genomic models as was recently confirmed in Norway spruce for growth, wood quality and weevil resistance traits (Lenz et al, 2020).…”
Section: Predictive Breeding Promises Boosting Forest Tree Genetic Immentioning
confidence: 82%
“…Yet, the power of population genomics must be further extended to comprehend neutral and adaptive processes in noncommercial species of ecological value in order to advance not just productivity, but also climate adaptation, forest health and conservation (Isabel et al, 2020). In this sense, GP is starting to permeate novel non-key traits other than growth and wood density, but still of interest for breeding, such as branching, stem straightness and external resin bleeding (Li et al, 2019). GP is also predicting adaptive trait variation for abiotic (Eckert et al, 2010) and biotic (Westbrook et al, 2020) stresses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations